Estimation of fetal weight using Hadlock's formulas: Is head circumference an essential parameter?. (December 2019) - Dakwar Shaheen, Joanna; Hershkovitz, Reli; Mastrolia, Salvatore Andrea; Charach, Ron; Eshel, Ron; Tirosh, Dan; Shaheen, Naim; Baron, Joel
Abstract: Objectives: To test the equivalence of two fetal weight estimation formulas generated by Hadlock, a formula that includes head circumference parameter (H1), and another (H2) which excludes this parameter. A secondary aim was to identify the patients in which H2 formula is less reliable to use. Study design: This retrospective cohort study included a total of 1220 sonographic fetal weight estimations performed within seven days of delivery and recorded at a single medical center from January 2014 to December 2016. Estimated fetal weight was calculated using H1 and H2 formulas. Their accuracies were compared using percentage error, the proportion of weight estimations falling within ±15% error interval and by Bland-Altman analysis. Multivariate regression was performed to evaluate factors affecting weight estimation by H2 formula. Results: The mean birth weight was 3288.92 ± 641.27gr. The H2 formula presented with statistically significant higher value of systemic mean percent error comparing to H1 (3.19% vs. 1.87%, p < 0.001 respectively). H2 formula had a lower accuracy compared to H1 in predicting fetal weight within ±15% of birth weight (90.49% vs. 93.44%, p < 0.01 respectively). Using Bland-Altman analysis, the 95% limits of agreement between both formulas were (-142.03) to 231.79gr with a mean of 44.88gr. Factors found to influence significantly on H2 formula were long femur length (OR 1.144, p < 0.0001) and low maternal age (OR 0.947, p < 0.01). Conclusions: H1formula was more accurate than H2 formula in predicting fetal weight at term. However, the accuracy difference was found to be small. Therefore, if ultrasonographic evaluation of HC is technically difficult, Hadlock formula that excludes head circumference can be used with confidence. Caution should be paid with higher values of femur length and lower maternal age.